DAYA SAING EKSPOR KARET ALAM TIGA NEGARA ITRC (INDONESIA, THAILAND, MALAYSIA) DI PASAR INTERNASIONAL PERIODE 1994-2018 - Ardanari, Shinta Dwi; Mukiwihando, Rynalto (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2020)
ABSTRACTShare of Indonesia's export value of natural rubber in the international market is almost always below Thailand, which is one of the competiting countries. The others countries began to become a threat to Indonesia because their exports share of natural rubber showed an increasing. This indicates that there is intense competition in the international market. As a country with the largest plantation area in the world, Indonesia should be superior. But this can be an opportunity to be able to compete in the world market so it is important to be managed more deeply so that it can create competitive advantages that can increase competitiveness. This study aims to determine the position of the competitiveness of natural rubber exports for the three countries of ITRC in the international market. The analytical method used is dynamic RCA. The results showed that all products of natural rubber coded HS 400110, 400121, 400122, 400129 and 400130 were experiencing a decline in growth in the export share of the three countries of ITRC : Indonesia, Thailand and Malaysia, but the market demand conditions for these products were declining in that time period.